Delivery of mesenchymal stem cells-derived extracellular vesicles with enriched miR-185 inhibits progression of OPMD. Issue 1 (4th December 2019) - Wang, Lin; Yin, Panpan; Wang, Jiaqi; Wang, Yuanyuan; Sun, Zheng; Zhou, Yu; Guan, Xiaobing
Abstract: Oral leukoplakia is one of the most common oral potentially malignant disorders (OPMDs) and its malignant transformation to oral cancer is highly associated with chronic inflammation. Extracellular vesicles (EVs) or exosome-delivered microRNAs modulate inflammatory responses and alleviate irritations that predisposes to cancer. We previously reported that microRNA-185 (miR-185) was significantly decreased in the buccal tissue of patients with oral cancer. In this study, we utilized genetically modified mesenchymal stem cells (MSCs) derived EVs with high expression of miR-185 to pasted MSC-EV-miR-185 on buccal lesions in dimethylbenzanthracene (DMBA) induced OPMD model. We found that treatment with MSC-EV-miR-185 remarkably attenuated inflammation severity and significantly decreased the incidence and the number of dysplasia in the OPMD tissue. Immunohistochemistry showed significantly decreased expression of proliferation marker PCNA and angiogenic marker CD31 in the lesion treated with MSC-EV-miR-185. Furthermore, miR-185 specifically targeted Akt genes by promoting activation of the apoptotic pathway, confirmed by the increased levels of activated caspase-3 and 9. In conclusion, genetically modified MSC-derived EVs enriched with miR-185 alleviate inflammatory response, inhibit cell proliferation and angiogenesis, and induce cell apoptosis, suggesting that their potential role as a novel therapeutic option for OPMD.